TRANSFORMASI HUKUM WARIS ISLAM TERHADAP KEPEMILIKAN ASET DIGITAL: PENDEKATAN MAQĀṢID AL-SYARĪ‘AH - Hamdani Cibro (STKIP Subang, 2026)
Abstract The rapid advancement of digital technology has created various forms of digital assets with significant economic value, including digital wallets, cryptocurrencies, monetized social media accounts, non-fungible tokens (NFTs), and cloud-based digital storage. This development has raised legal challenges because Islamic inheritance law has not explicitly regulated the inheritance mechanism for digital assets. This study aims to analyze the transformation of Islamic inheritance law concerning digital asset ownership through the perspective of Maqāṣid al-Sharī‘ah. This research employs a normative legal method using conceptual, statutory, and Maqāṣid al-Sharī‘ah approaches. Data were collected through library research involving the Qur'an, Hadith, the Indonesian Compilation of Islamic Law, statutory regulations, academic literature, and previous studies. The data were analyzed using descriptive qualitative techniques. The findings indicate that digital assets fulfill the concept of māl (property) in Islamic law and therefore may become inheritable property when legal ownership can be established. The principles of Maqāṣid al-Sharī‘ah, particularly ḥifẓ al-māl (protection of property), provide a normative foundation for reconstructing Islamic inheritance law to ensure legal certainty, justice, and public benefit in the transfer of digital assets in the digital era.